Pengaruh Model Pembelajaran Treffinger Dalam Keterampilan Menulis Teks Negosiasi Berbantuan Media Sinego (Simulasi Negosiasi) - Sarah, Siti; Kartikasari, Ratna Dewi (Politeknik Amamapare, 2026)
This study aims to determine the effect of the Treffinger learning model on negotiation text writing skills assisted by SINEGO (Negotiation Simulation) media. This study uses a quantitative approach with a quasi-experimental method. The research design used is a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class that implemented the Treffinger learning model assisted by SINEGO media and the control class that used the conventional learning model. The data collection technique was carried out through a negotiation text writing skills test. The data obtained were analyzed using normality tests, homogeneity tests, and hypothesis tests with t-tests. The results of the study showed that the negotiation text writing skills of students taught using the Treffinger learning model assisted by SINEGO media were better than those of students taught using conventional learning. This is evidenced by the average value of the experimental class which was higher than the control class and the results of the t-test which showed a significant difference. Thus, it can be concluded that the Treffinger learning model assisted by SINEGO media has a positive effect on students' negotiation text writing skills.